2000
DOI: 10.1103/physreve.62.3619
|View full text |Cite
|
Sign up to set email alerts
|

Convection in two-layer systems with an anomalous thermocapillary effect

Abstract: Recently, it was found that the anomalous thermocapillary effect (the interfacial tension increases with temperature) is typical for various liquid-liquid systems. We consider the combined action of buoyancy and thermocapillary instability mechanisms in systems with an anomalous thermocapillary effect on the interface. The problem is solved in both linear and nonlinear formulations. A special type of oscillatory instability has been found and investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…This conclusion should be regarded with some caution since it is based merely on a single simulation at each point (G, M). In any case, the numerical value of k of about 7k b ≈ 1.76 is in good agreement with linear stability results obtained by Braverman et al (2000). Linear The transition from steady to oscillatory convection as M and G are varied has been investigated by means of additional simulations.…”
Section: Competition Between Marangoni and Rayleigh Instability Mechasupporting
confidence: 83%
See 1 more Smart Citation
“…This conclusion should be regarded with some caution since it is based merely on a single simulation at each point (G, M). In any case, the numerical value of k of about 7k b ≈ 1.76 is in good agreement with linear stability results obtained by Braverman et al (2000). Linear The transition from steady to oscillatory convection as M and G are varied has been investigated by means of additional simulations.…”
Section: Competition Between Marangoni and Rayleigh Instability Mechasupporting
confidence: 83%
“…For instance, in the case of the total thickness a 1 + a 2 = 4 mm (K = 70.3), we find = 0.21 s −1 . In order to describe the main stages of oscillations, let us present some results of 2D simulations performed in the case G = 18, M = −3933 (for more details, see Braverman et al (2000)). …”
Section: Competition Between Marangoni and Rayleigh Instability Mechamentioning
confidence: 99%
“…On the other hand it has been known for some time [12,16] that a system of two superimposed liquids displays a much richer behaviour than the single layer models. In particular the Marangoni instability can be induced by heating from above such that buoyancy and thermocapillarity compete rather than enhance each other, a situation which in single layer systems can only be realized using the rare case of liquids with anomalous thermocapillary effect in which the surface tension increases with increasing temperature [17]. Many additional features such as oscillatory instabilities [18] or transitions from up-to down-hexagons may be found in systems with two liquid layers.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon was first discovered in the case of a two-layer system. 3,6,23,24 In the present paper, which is devoted to the investigation of the combined action of thermocapillary and thermogravitational mechanisms of instability in the multilayer system, we investigate a similar phenomenon. It is shown that if both, the Marangoni number M, and the Grashof number G, are different from zero, the specific type of oscillations can appear in the system.…”
Section: Introductionmentioning
confidence: 92%